كيفية حساب الأجر والراتب لدى مديرية التربية - فريدة, عيساوي; طارق, بن عبيد; ريحانة, العايز; عفاف, عشاب (جامعة الوادي - University of Eloued, 2023)
في هذا الفصل قمنا بتعريف المؤسسة محل دراسة و تطرقنا إلى نشأتها ومهامها و إنجازاتها المحققة وهيكل التنظيمي ثم خصصنا دراسة بمصلحة نفقات المستخدمين وبعد الاطلاع على نطم سير عملية حساب الأجور والرواتب بناء على النصوص التي تحكم قطاع التربية والإضافات وتغيرات الحديثة على جدول الضريبة على الدخل وأيضا كيفية حساب الأجور والرواتب وكيف تسدد هذه الأعباء على عاتق المؤسسة. "In this chapter, we have defined the institution under study, and we have touched on its inception, tasks, achievements, and organizational structure. Then, we devoted a study to the interest of employees’ expenses, and after examining the system of the process of calculating wages and salaries based on the texts governing the education sector, additions and recent changes to the income tax schedule, as well as how The calculation of wages and salaries and how to pay these burdens is the responsibility of the institution. "
Keywords: الأجور والرواتب, التعويضات, المنح وعلاوات, الاقتطاعات.; Wages and salaries, compensation, grants and bonuses, deductions.